Following Scale with Profits: Explaining Fino's Unlinkely Success - Joseph, Nikhil; Mazzotta, Benjamin D (Tufts Archival Research Center, 2019)
Cost of Cash|Inclusive Growth|IBGC Working Paper WP14-06